Kedudukan Laki-Laki Nyentana pada Wanita yang Memiliki Saudara Laki-Laki di Desa Bantas Kabupaten Tabanan - I Gede Pasek Darsana Wiratama; I Ketut Sukadana; Diah Gayatri Sudibya (Jurnal Konstruksi Hukum, 2020)
Marriage is a very important thing in human life, with the aim of forming a household. In Balinese society, there is a nyentana marriage, in which a family does not have a son. However, along with the development of families in Bali, they married Nyentana even though they had a son for certain reasons. The formulations of the problems in this study are: 1) What is the position of men who are sedentary according to Balinese customary law? 2) How do men inherit rights to women who have brothers? This type of research is empirical law. The approach to the problem used is sociology of law. The data used are primary data obtained from field studies by interviewing informants. Secondary data were obtained from literature study. The result of this research is the position of men who are sedentary according to Balinese customary law as predana, in general, have the same rights and obligations as men in the family. These rights and obligations are like those of a family head in general. The right to inherit male nyentana to women who have brothers is said to be abolished because the male only continues the offspring in the wife's family.